HIDDEN POWER DALAM POLITIK PEMEKARAN DI NUSA TENGGARA TIMUR - Beli, Welhelmina Selfina (JOURNAL OF GOVERNMENT (Kajian Manajemen Pemerintahan dan Otonomi Daerah), 2016)
Proliferation of regions phenomenon can be likened to a "mushroom" which thrives everywhere, from the years 1999 until 2013 have been formed so many New Autonomous Region, but the presence of New Autonomous Region is not an answer to the problems faced by the community. Monopoly power and political and economic interests are always the basis for the formation of new regions. The research with the title “hidden power in the expansion of political power in East Nusa Tenggara” will analyze about the political forces hidden in the politics of division that occurred in East Nusa Tenggara. The method used in this research is descriptive qualitative. The focus of this research is on the proliferation of Pantar Region of East Nusa Tenggara province. The analysis relied on data of primary and secondary data obtained through document analysis and in-depth interviews.Results from this research is indicate that the interests of the local elite politic are more dominant in terms of struggling power by selling the Splitting issue of Pantar region. The hidden power that comes from a group of individuals who support the division by taking advantage of the process. In addition there is the ethnic element in the expansion process, because it appears that the inception of the committee is dominated by a particular ethnic division.   Keywords: Political regional expansion, hidden power, proliferation of region  in East Nusa Tenggara